2020
DOI: 10.3233/adr-200250
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis is a Strong Risk Factor for Alzheimer’s Disease

Abstract: Porphyromonas gingivalis (P. gingivalis) is one of the several important bacterial pathogens associated with the sporadic Alzheimer’s disease (AD). Different serotypes are either capsulated or are non-capsulated. It has been demonstrated that P. gingivalis (non-capsulated) can reproduce the neurodegenerative AD-like changes in vitro, and a capsular P. gingivalis (strain W83) could reproduce the cardinal hallmark lesions of AD in a wild-type mouse model. All P. gingivalis forms express proteolytically active pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 95 publications
1
51
0
8
Order By: Relevance
“…There is increasing evidence implicating the polymicrobial infection with P. gingivalis as playing a part in disease pathogenesis, not only from the low-grade inflammation but the actual translocation into the brain vasculature [64]. A link between Alzheimer's and P. gingivalis in the brain is consistent with this emerging model for microbes in the disease's etiology [58,[73][74][75].…”
Section: Inflammatory Pathogensmentioning
confidence: 74%
“…There is increasing evidence implicating the polymicrobial infection with P. gingivalis as playing a part in disease pathogenesis, not only from the low-grade inflammation but the actual translocation into the brain vasculature [64]. A link between Alzheimer's and P. gingivalis in the brain is consistent with this emerging model for microbes in the disease's etiology [58,[73][74][75].…”
Section: Inflammatory Pathogensmentioning
confidence: 74%
“…Fifteen peptides were tested against several bacterial and fungal strains, but only three peptides showed antibacterial and antifungal activity. P. gingivalis is a human pathogenic bacteria causing periodontitis [ 32 , 33 ], and its noted association with other disease like Alzheimer’s disease [ 34 , 35 ] is a serious threat to human health. Identifying novel drug candidates against P. gingivalis will add value to a treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported an association between periodontitis and AD [19][20][21][22][23][24][25][26][27][28]. Several reports have suggested how virulence factors of P. gingivalis can contribute to AD, particularly LPS, gingipains, PPAD (P. gingivalis peptidylarginine deiminase), Mfa1 fimbrial protein, BCAT (branched-chain amino acid aminotransferase), and capsular polysaccharides [29][30][31][32][33][34].…”
Section: Relationship Between Periodontitis and Alzheimer's Diseasementioning
confidence: 99%